Wild bee diversity of the National Park of the Semois Valley (Belgium) - Maxence Gérard; William Fiordaliso; Louise Ferrais; Chloé Fournier; Malo Hairault; Lise Lheureux; Paolo Rosa; Guillaume Ghisbain (Biodiversity Data Journal)
Wild bees are essential pollinators, yet their decline due to human activities threatens ecosystem stability. Protecting these pollinators requires a detailed understanding of both their diversity and distribution. In Belgium, the recently-established Semois Valley National Park (SVNP) is located in a region with limited bee sampling data and this study aims to identify the habitats most suitable to bees, especially for threatened species.Over five months, we surveyed 32 sites and collected a total of 1,119 specimens belonging to 120 bee species. Twenty-two of the observed species are listed as threatened in Belgium according to the last Red List published in 2019 for the country, four of them being Critically Endangered. Our findings indicate that mesic grasslands support the highest species diversity, as well as the highest number of threatened species. Our results underscore the need for conservation efforts aimed at maintaining diversity and species richness in this region. Effective biodiversity preservation will require enhanced habitat management and strategies tailored to bee species' ecological requirements.